Student Perception of the Quality of Personal Efforts and Learning Outcomes in a Virtual Environment - Popa, Doinița (Didactica Danubiensis, 2023)
The paper presents the results of a study on Danubius University students' perception of the quality of personal efforts and learning outcomes in a virtual environment. This study is based on a tool that identified students' views on learning outcomes using the E-Learning DO - Sakai platform, to find the most effective ways to improve online learning in the coming period. The aspects pursued were structured on the following fields: Overall Experience with Distance Education, Distance Education Infrastructure, Distance Education Tools, Pedagogical Successful, and Personal Profile of the student.